Perspectives of older adults about their present situation and future projection : Reflection workshops - Ciano, Natalia (2019)
In this paper, the results obtained on the perspectives of older adults are presented, particularly in relation to their present situation and future projection. 85 older adults (65 women and 20 men) who took part in different institutions of La Plata City were included. The reflection workshops were in general about aging, psychological and social changes and considerations on the time dimension that they bring. Implementing these workshops about the mentioned themes has allowed us to establish some issues of interest to develop, design and carry out a specific process of guidance for older adults, in which the protagonist is the subject with its desires and interests, as we conceive that in guidance it is essential to consider the singularity, to support them during the aging process (in some cases marked by retirement), so the older adults can question themselves about their new possibilities, can decide where to be involved, question themselves about interests, motivations and desires, often postponed, since it is not about spend the spare time, but to make new projects and achieve them.